DEVELOPMENT AND VALIDATION TEST OF DISINI (DISTAL SYMETRIC NEUROPATHY) IN DIABETES MELLITUS PATIENTS - Maharani, Anyelir Dewi; Pinzon, Rizaldy Taslim; S, Sugianto (MNJ (Malang Neurology Journal), 2025)
Background: Diabetic neuropathy is a complication of diabetes mellitus that may lead to ulceration and potentially amputation of the feet in affected individuals. This may result in elevated rates of morbidity and mortality. Although certain health care facilities lack access to essential neuropathy screening equipment (e.g., 128 Hz tuning forks, reflex hammers, and monofilaments), alternative methods must be developed to ensure early detection of diabetic neuropathy. Objective: To determine the development and measure the validity of the DISINI (Distal Symmetric Neuropathy) questionnaire in diabetes mellitus patients. Methods: A quantitative cross-sectional analysis was conducted at Bethesda Hospital Yogyakarta utilising secondary data obtained from DISINI and DN4 examinations of 64 individuals diagnosed with diabetes mellitus. Utilising the ROC curve, AUC value, Pearson correlation test, and Spearman rank correlation, the acquired data were analysed. Results: Analysis of the ROC Curve and AUC values showed that the cut off for the DISINI questionnaire was ≥ 3. The diagnostic value of the DISINI questionnaire included sensitivity 91.84%, specificity 60.00%, positive predictive value (NPP) 88.24%, negative predictive value (NPN) 69, 23%, positive likelihood ratio (LR (+)) 2.30, and negative likelihood ratio (LR (-)) 0.14. The correlation test DISINI with DN4 shows that there is a relationship between the scores of the DISINI  and DN4 (p = 0.001). The correlation test between DISINI and DNE shows that there is a relationship between the DISINI and DNE scores (p = 0.013). The correlation test DISINI with DNS shows that there is a relationship between the scores of the DISINI and DNS (p = 0.007). The correlation test DISINI with Monofilament showed that there was no relationship (p = 0.318). Conclusion: The validation test of the DISINI (Distal Symmetric Neuropathy) questionnaire in diabetes mellitus patients had a sensitivity of 91.84% and a specificity of 60.00% using the gold standard DN4 (Douleur Neuropathique en 4 Questions).